SYNTHETIC APPROACH TO THE DEVELOPMENT OF TECHNOLOGY FOR MANUFACTURE OF COLD-DEFORMED REINFORCEMENTS IN ACCORDANCE WITH THE REQUIREMENTS OF TECHNICAL REGULATIONS AND MARKET - V. V. Belash (Литьë и металлургия, 2018)
The article represents a synthetic approach to the development of technology for manufacture of cold-deformed reinforcement tailored to the needs of the market, which needs to have cold-worked reinforcement with negative field of tolerance on the linear density.